PREDIKSI KEBUTUHAN RAK DOKUMEN REKAM MEDIS DI RUMAH SAKIT PERMATA BUNDA TAHUN 2022-2026 - Gunawan Gunawan; Karina Permata Devi (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2022)
Medical record documents (DRM) at Permata Bunda Hospital are added every year, especially new DRM. The addition of new DRM causes the shelves to be full and exceed the storage capacity so that there are 2600 active DRM stored in cardboard. The addition of DRM causes less storage space. The process of shrinking and destroying DRM at Permata Bunda Hospital has not been carried out routinely so that inactive files accumulate in the storage room. The narrowing of storage space makes it difficult for medical record officers in the return and retrieval process. A fast and accurate return and retrieval process is needed to maintain the quality of DRM services. Planning for five-year (2022-2026) DRM storage rack requirements is very important. This study aims to determine the prediction of the need for DRM shelves at Permata Bunda Hospital in 2022-2026. The type of research used is descriptive quantitative. There are 73,575 (2019-2021) medical DRM as the population and 100 DRM used as the sample. Collecting data by direct observation and calculation on the specified variable. Analysis of calculations with linear equations trend of the last 3 years. The results of the study were 29,452 new DRM and 44,123 old DRM in the 2019-2021 period. The average thickness of the DRM is 0.235 cm. The results of the calculation of the prediction of DRM shelf needs in 2022-2026 are that 18 additional shelves are needed and an area of 8.4 m x 8.7 m = 73 m2